Super-Resolution Imaging Approaches for Quantifying F-Actin in Immune Cells - Garlick, Evelyn; Thomas, Steven G.; Owen, Dylan M. (Frontiers in Cell and Developmental Biology, 2021)
Immune cells comprise a diverse set of cells that undergo a complex array of biological processes which must be tightly regulated. A key component of cellular machinery that achieves this is the cytoskeleton. Therefore, imaging and quantitatively describing the architecture and dynamics of the cytoskeleton is an important research goal. Optical microscopy is well suited to this task. Here, we review the latest in the state-of-the-art methodology for labelling the cytoskeleton, fluorescence microscopy hardware suitable for such imaging and quantitative statistical analysis software applicable to describing cytoskeletal structures. We also highlight ongoing challenges and areas for future development.